Attribution of Liability in Transboundary Water Pollution Incidents - Ren, Zhen (Journal of Current Social Issues Studies, 2025)
The issue of attribution of liability for transboundary water resource pollution involves a large number of stakeholders. It is necessary to analyse the ambiguities in the liability in the light of the legal basis and the practical orientation, and to find a way forward to improve clarity and enforceability. It is crucial to clarify the liability and compensation mechanism, which not only needs to follow the basic principles of international environmental law, such as common but differentiated responsibilities and sustainable development, but also draws on international treaties and judicial practice. Besides, At the same time, it is also important to pay attention to the fact that China has already gained some influence in the international community in the area of liability determination for transboundary water pollution, including the management of transboundary water resources based on sovereignty and co-operation, the construction of a legal system using a combination of soft and hard law, and the establishment of an ecological compensation mechanism. In order to enhance the clarity and operability of international liability norms in line with the international process, China can refer to international practices and achieve its goals by promoting transboundary water resources cooperation, strengthening legal enforcement and cross-border accountability, and improving emergency preparedness and liability implementation.